Occurrence and trends of musculoskeletal pain among ski instructors - Denis Čaušević; Erol Kovačević; Semir Mašić; Siniša Kovač; Seth Spicer (IP Iermakov S.S., 2022)
Background and Study Aim. Musculoskeletal disorders (MSD) are incredibly common and are often related to work load. For any occupational or public health intervention, injury prevention is preferred to injury treatment. Occupational health and injury prevention research has the potential to help mitigate MSD in the workplace. The aim of this study was to determine how the work demands of ski instructors may affect the health of their musculoskeletal system. Material and Methods. A cross-sectional study involved the participation of 87 ski instructors (age = 34.61 ±10.67) in Bosnia and Herzegovina (ATUS in Bosnia and Herzegovina). Observed variables were the prevalence of MSD measured using a modified Nordic questionnaire about injuries during the previous ski season (neck, shoulders, elbows, wrist, upper back, lower back, one or both hips, one or both knees, and ankle). Means and standard deviations for each of the variables were calculated, and differences between genders were examined using an independent sample t-test. Results. Prevalence of MSDs in ski instructors was most common in neck (13.8%), shoulders (12.6%), elbows (4.6%), wrist (9.2%), upper back (10.3%), lower back (46.0%), one or both hips (9.2%), one or both knees (29.9%), and ankle (9.2%). The results showed statistically significant differences in MSD between genders in the neck (p=.034); shoulders (p=.017); upper back (p=.027); one or both knees (p=.003) and in the ankle joint (p=.011). Conclusions. MSD's are common in ski instructors, especially in the low back and knees of female employees. Future research or injury prevention programs would benefit these populations.